Endosomal TLR-8 Senses microRNA-1294 Resulting in the Production of NFḱB Dependent Cytokines - Pluta, Linda; Yousefi, Babak; Damania, Blossom; Khan, Asma A. (Frontiers in Immunology, 2019)
The primary function of toll-like receptor 8 (TLR-8) is the detection of viruses and other microbial pathogens. Recent evidence suggests that TLR-8 also senses host microRNAs (miRNAs) and implicate TLR-8 in autoimmune disorders. This study examined the interaction between miR-1294 and TLR-8. We first performed a BLAST search to identify miRNAs with the same sequences as two core motifs of miR-1294. Next, we examined NFḱB activation induced by the binding of miR-1294 mimic to endosomal TLR-8. HEK-Blue™ hTLR-8 cells (Invivogen), a HEK293 cell line co-transfected with human TLR-8 gene, were incubated with miR-1294 mimic. A TLR-8 agonist ssRNA40, was used as a positive control. Using the same experimental set up, we also examined the effects of miR-1294 and its two core motifs (Integrated DNA Technologies) on IL-8, IL-1β and TNFα. Data were analyzed using t-test or one-way ANOVA and Dunnets Post-hoc test. Using miRCarta we identified 29 other mature human miRNAs or their precursors which contain the same core motifs as miR-1294. Our data show that miR-1294 activates NFḱB in cells expressing TLR-8 (p<0.05). miR-1294, and its core motifs induce expression of IL-8, IL-1β and TNFα via TLR8 activation (p<0.05). This constitutes a novel mechanism by which endosomal TLR-8 senses host miRNAs resulting in the release of pro-inflammatory cytokines and thus potentially contributing to autoimmune disorders.